Addressing Social Determinants of Health in a Free Clinic Setting: A Student-Run Free Clinic and Community Resource Navigator Program - Alyssa Fleischman; Claire Vanden Heuvel; Dahlia Tesfamichael; Taryn McGinn Valley; Kristina Jones (Journal of Student-Run Clinics, 2023)
AbstractBackground: Social determinants of health (SDOH) disproportionately affect medically underserved populations such as those cared for in student-run free clinics (SRFCs). Community resource programs which address SDOH play an important role in reducing health disparities. The Southside MEDiC Clinic (SMC), a SRFC at the University of Wisconsin School of Medicine and Public Health, partnered with the Community Resource Navigator Program (CRNP), a community resource program focused on addressing SDOH, to remove barriers that prevent positive health outcomes for SMC patients.Aim: Our objective is to describe the partnership between the SMC and the CRNP. We hope this design may be used as a model for addressing SDOH in other SRFCs.Discussion: Partnership goals include improved patient perception of health, increased communication between patients and the clinic, and enhanced opportunities for volunteer action-learning. Challenges discussed include adaptation to unique clinics. Future directions and potential advancements in this partnership are also addressed.